Design and Study UAV Data Link Terminal with One Station Controls Several Vehicles Dynamic Networking. Issue 5 (April 2020) - Junkai, MA; Wang, Xiaoyan; Chen, Kewei; Liu, Qingtao
Abstract: Considering that there are UAVdynamic networking and collaborative communication requirements under complex mission planning conditions, this paper designs a UAV data link communication terminal with One Station Controls Several Vehicles dynamic networking. Firstly, this paper analyzes the structure of One Station Controls Several Vehicles dynamic networking and cooperative communication system in UAV data link, and combines the characteristics of dynamic networking and task cooperative communication to design a One Station Controls Several Vehicles dynamic networking communication protocol stack and design the structure and function of the man-machine data link, the terminal device hardware is realized by the FPGA chip. This paper focuses on digital zero-IF signal processing unit design and hardware implementation process. Finally, combined with the terminal to build an indoor test environment, this paper tests the network function and performance. The test results prove that the UAV data link terminal in One Station Controls Several Vehicles dynamic networking is effective, and it is practical.